Depression and Diabetic Peripheral Neuropathy: Birds of a Feather, But When do They Flock Together? - Vas, Prashanth R.J.; Papanas, Nikolaos (Experimental and Clinical Endocrinology & Diabetes, 2020)
The association between diabetes and depression is well recognised. Similarly, diabetic peripheral neuropathy (DPN) is a frequent complication of diabetes. Given the high prevalence of these conditions individually, it is hardly surprising they frequently interact, conferring additional morbidity and a higher mortality risk. Despite this, the specific clinical characteristics that underpin co-morbid depression and DPN remain unclear. Additionally, there is insufficient insight into causal pathways and temporal trends. High-quality epidemiological data is limited, but they suggest that these conditions may share certain common risk factors, although there are also distinct differences such as gender. Improved insights into the risk factors for the co-existence of DPN and depression may help towards improved screening for and treatment of these conditions.